A Creator’s Illness as a Source of Memory and Forgetting: Selected Examples - Darska, Bernadetta (Tematy i Konteksty, 2021)
In the present article I examine autobiographical works in which writers reveal their illnesses. I am interested not so much in the description of a given ailment, but rather in the embroilment resulting from being ill and from the persistent conflict between memory and forgetting. Becoming aware of the illness turns out to be a critical point, forcing the writers to re-evaluate their own lives. Consequently, memory and forgetting assume a new status. I also attempt to juxtapose the universal nature of being ill and the intimacy of this experience; I point out the similarities and differences involved in dealing with illnesses, the common denominator of which seems to be the necessity of confronting the limits of memory and the expansiveness of forgetting.